Short-term results of acupuncture in endovenous ablation treatment: Status of pain and patient satisfaction (Annals of Medical Research, 2021)
Aim: Our aim was to investigate the results of acupuncture in endovenous ablation treatment at 6–9 months.Materials and Methods: Group C (control,n=35) and Group A (acupuncture,n=35) patients included in this study were called by the cardiovascular surgeon for 6–9-month check-ups.Demographic characteristics, visual analogue scale (VAS) score,6–9 months saphenous vein diameter,patient satisfaction,CEAP classification, and other findings were recorded in both groups. Results: There was no difference between the groups in terms of age and body mass index.Patient satisfaction was higher in Group A (p=0.040).VAS scores were higher in Group C (p =0.002).There was an increase and a decrease in the saphenous vein diameter values of the patients at 6–9 months compared to the baseline values in Group C (p=0.004) and Group A (p=0.011),respectively.There was a decrease in the CEAP classification of the patients in Group C at 6–9 months compared to the baseline values (p=0,000).In Group A,there was a decrease in the CEAP classification of the patients at 6–9 months compared to the baseline values (p =0,000).In Group C,erythema 2 (5.7%),edema 7 (20.0%),and ıtching 7 (20.0%) were seen in the patients.In Group A, edema 3 (9.3%),itching 2 (5.8%),but not erythema were seen in the patients.In Group A, 34 of 35 patients stated their desire to recieve acupuncture again.Conclusion: Acupuncture increased patient satisfaction and reduced VAS scores and CEAP classification at 6–9 months.Acupuncture affected the saphenous vein diameters positively.There were less complications in the acupuncture group at 6–9 months.
Keywords: Acupuncture; pain; patient satisfaction; varicose veins